Development of a Website-based Inventory Information System at Konveksi Mitra Jaya Abadi - Indrianita, Dian; Napianto, Riduwan (Sistemasi: Jurnal Sistem Informasi, 2025)
The utilization of information technology has increased the demand for more efficient and accurate inventory management systems, particularly for businesses such as Mitra Jaya Abadi Garment Company, which previously relied on manual record-keeping. This study aims to design and implement a web-based inventory information system using the Extreme Programming (XP) methodology. XP was chosen for its flexibility in software development and its support for direct user involvement in the iterative process. The system was developed using the CodeIgniter framework and applied the Model-View-Controller (MVC) architecture to ensure a clear separation between application logic, user interface, and data management. Compared to the previous system, the new system provides more flexible reporting features, including filters by date and item category, as well as report export capabilities. Unlike the waterfall approach, the XP methodology allows for faster iterations, better adaptability to changing requirements, and stronger user engagement. System testing based on the ISO 25010 standard demonstrated excellent feasibility, achieving an overall score of 95.36%. The system is expected to accelerate and simplify inventory management processes, reduce errors in data recording, and improve the efficiency of decision-making.